Developing domain‐specific AI‐based tools to boost cross‐enterprise knowledge reuse and improve quality. Issue 1 (20th September 2021) - Sarwar, Sajjad; Haskins, Cecilia
Abstract: MHWirth observed that several quality issues surfaced during the product commissioning phase causing a negative impact on project cost, delivery time and customer satisfaction. By using root cause analyses, this research found several links between poor quality and lack of proper knowledge management. With better knowledge management, most of these quality issues could be addressed and solved at an earlier stage of the product life cycle. Today different barriers are preventing organizations from taking full advantage of previously generated valuable knowledge. This paper explores how the use of Artificial Intelligence can boost knowledge reuse. The goal is to empower faster and more informed decision‐making based on lessons learned in the past to minimize waste, rework, re‐invention and redundancy.